2020
DOI: 10.1021/acs.orglett.9b04606
|View full text |Cite
|
Sign up to set email alerts
|

Homoleptic Bis(trimethylsilyl)amides of Yttrium Complexes Catalyzed Hydroboration Reduction of Amides to Amines

Abstract: Homoleptic lanthanide complex Y­[N­(TMS)2]3 is an efficient homogeneous catalyst for the hydroboration reduction of secondary amides and tertiary amides to corresponding amines. A series of amides containing different functional groups such as cyano, nitro, and vinyl groups were found to be well-tolerated. This transformation has also been nicely applied to the synthesis of indoles and piribedil. Detailed isotopic labeling experiments, control experiments, and kinetic studies provided cumulative evidence to el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…The catalytic deoxygenative hydroboration of amides to amines is a safe alternative to hydrogenations or the use of LiAlH 4 . Rare earth metal catalysts were recently reported;[ 7f , 7g , 17 ] an abnormal N ‐heterocyclic carbene‐potassium catalyst was active at 40 °C; [20] the combination KO t Bu/BEt 3 enabled amide reductions at 25–60 °C with pinacolborane; [21] 2,6‐di‐ tert ‐butyl‐phenolate lithium‐THF was catalytically active at 60 °C. [22] The simple pre‐catalyst Mn(hmds) 2 proved active in the hydroboration of alkyl and aryl carboxamides with pinacolborane to primary amines in very good yields at 50 °C (Scheme 3 , center).…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic deoxygenative hydroboration of amides to amines is a safe alternative to hydrogenations or the use of LiAlH 4 . Rare earth metal catalysts were recently reported;[ 7f , 7g , 17 ] an abnormal N ‐heterocyclic carbene‐potassium catalyst was active at 40 °C; [20] the combination KO t Bu/BEt 3 enabled amide reductions at 25–60 °C with pinacolborane; [21] 2,6‐di‐ tert ‐butyl‐phenolate lithium‐THF was catalytically active at 60 °C. [22] The simple pre‐catalyst Mn(hmds) 2 proved active in the hydroboration of alkyl and aryl carboxamides with pinacolborane to primary amines in very good yields at 50 °C (Scheme 3 , center).…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic deoxygenative hydroboration of amides to amines is a safe alternative to hydrogenations or the use of LiAlH 4 . Rare earth metal catalysts were recently reported; [7f,g, 17] an abnormal N ‐heterocyclic carbene‐potassium catalyst was active at 40 °C; [20] the combination KO t Bu/BEt 3 enabled amide reductions at 25–60 °C with pinacolborane; [21] 2,6‐di‐ tert ‐butyl‐phenolate lithium‐THF was catalytically active at 60 °C [22] . The simple pre‐catalyst Mn(hmds) 2 proved active in the hydroboration of alkyl and aryl carboxamides with pinacolborane to primary amines in very good yields at 50 °C (Scheme 3, center).…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, Ye et al studied the performance of the akin complex Y[N(SiMe 3 ) 2 ] 3 ( 5 ), which was also examined in Marks' report albeit not as selected catalyst and proposed a distinct mechanism for the hydroboration of amides (Scheme 23). [ 46 ] In the work by Ye et al, they successfully isolated the partially reduced imine as intermediate that underwent further conversion to final amine when subjected to the optimized conditions. Together with the kinetic studies, the authors concluded that metal hydride is involved in the catalytic cycle although the pathways for secondary and tertiary amides are slightly different.…”
Section: Hydroboration Of C–hetero Unsaturated Bonds: Aldehydes Keton...mentioning
confidence: 99%